THE IMPLEMENTATION OF RECIPROCAL TEACHING MODEL TO IMPROVE STUDENTS’ ACHIEVEMENT ON ACID-BASE CONCEPTS - Maysara Maysara; Habiddin Habiddin (Universitas Negeri Malang, 2019)
This study aimed to describe the improvement of students’ learning outcomes using reciprocal teaching model. The improvement is measured based on the results of pre-test and posttest. 24 students of XI class at SMA Negeri 4 Wangi-Wangi taking sciences major participated in this study. This one group pre-test & post-test research design used an instrument (test) in the form of multiple-choice questions. The questions were constructed by considering the cognitive level in Bloom taxonomy. The study reveals that students’ improvement falls in the moderate category with the N-gain score of 0.69. The study also uncovered that students’ ability in answering questions decreases with the increase in the cognitive level of the questions